KESANTUNAN TINDAK TUTUR DALAM INTERAKSI AKADEMIK - Muhammad Saleh; Baharman Baharman (Universitas Negeri Makassar, 2012)
This study aimed to describe and explain the propriety of speech act in academic interactions. This study includes the type of qualitative research using ethnography of communication design theory, speech act theory, and the theory of linguistic politeness. The research data consists of data conversations and field notes. Data collected through recording techniques, observation, interviews, and transcriptions. Data analysis was carried out through four main procedures, namely: data collection, data reduction, data presentation, and conclusions/verification. Based on data analysis, politeness of speech act are classified into four, namely: (1) civility in act assertively, (2) acts of civility in the directive, (3) civility in commissive act, and (4) civility in expressive acts.